The Testimonial “We”: Collaborative Life Writing in Senthuran Varatharajah’s Vor der Zunahme der Zeichen - Irene Kuo (Studies in 20th & 21st Century Literature, 2025)
In contemporary novels about refugees’ experiences, the subject of first-person witness often serves narratively as a means of centering the voices of those forcibly displaced. This reading of Senthuran Varatharajah’s novel Vor der Zunahme der Zeichen examines how the novel diverges from a focus on the singular testimony of a first-person subject to enable political recognition of shared experiences of flight. In its structure as a Facebook conversation between two strangers, Senthil and Valmira, sharing distinct experiences about arriving in Germany as asylum-seekers, Vor der Zunahme privileges a dialogue that underscores how their life histories are embedded in family histories and cultural memories of major historical events such as the Sri Lankan Civil War and Kosovo War. While previous readings of Vor der Zunahme have focused on its portrayal of trauma and language (Fagan), postdigital practices (Ubieto), peripherality (Majkiewicz), and conditions of displacement (Teupert) and cosmopolitanism (Lizarazu), this article considers how the novel engages social media to center the interpersonal aspect of life writing and reflect on forms of witnessing the transgenerational and cultural-historical aspects of personal narratives about flight and diasporic experiences.
Keywords: Senthuran Varatharajah; Vor der Zunahme der Zeichen; Before the Increase of Signs; The Sri Lankan Civil War; The Kosovo War; Sri Lankan Tamil diaspora; Albanian diaspora; postmemory; collective history; life writing